Case Report: Subgaleal drainage removal results in a fatal complication after burr-hole evacuation of chronic subdural hematoma - Karamani, Lydia; Januzi, Donjetë; Eckard, Niklas; Senft, Christian; Baumgarten, Peter (Frontiers in Surgery, 2025)
Placement of a drain in subgaleal space in the management of chronic subdural hematomas is a common technique. Subgaleal drains are considered a safe, effective and minimally invasive technique with low-complication rate. In this report, we present a rare but tragic adverse complication following the removal of a subgaleal drainage in a patient who had undergone an evacuation of a subdural bleeding. Although existing data indicates that the risk of cortical surface damage during drain removal is minimal, one must be aware of rare complications such as inadvertent injury to subcutaneous vascular structures culminating in an acute subdural hematoma.